Two-agent single machine scheduling with forbidden intervals - Feng, Qi; Li, Shi-sheng; Shang, Wei-ping (Applied Mathematics-A Journal of Chinese Universities, 2015)
We consider the resumable version of the two-agent single machine scheduling problems with forbidden intervals in which the jobs cannot be processed. The goal is to minimize the sum of the objective functions of the two agents. Polynomial and pseudo-polynomial time algorithms are presented for various combinations of regular scheduling objective functions.